Chlorinated organophosphate esters in Brazilian solid waste: concentrations, national load estimates, and regulatory implications for a circular economy - Hansel David Burgos Melo; Rafael Veronez; Juliana de Souza-Araujo; Angie Paola Santacruz Salas; Olumide Emmanuel Akinrinade; Sandro Donnini Mancini; Daniel Drage; Stuart Harrad; André Henrique Rosa (Environmental Pollution, 2026)

Distribution characteristics and ecotoxicological risks of typical organic flame retardants and plasticisers in the Amazon River basin around Manaus, Brazil - Yulong Ma; Angie Paola Santacruz Salas; Hansel David Burgos Melo; Shijie Wang; Jingxi Jin; Ezio Sargentini Júnior; André Henrique Rosa; Stuart Harrad (Environmental Research, 2026)

Seasonal variation of microplastics in indoor environments from Birmingham, UK: Implication for ingestion and inhalation exposure - William A. Stubbings; Hassan Khalid Ageel; Stuart Harrad; Mohamed Abou-Elwafa Abdallah (Chemosphere, 2026)

Ionic PFAS in PM2.5 and dust: Insights on indoor-outdoor profiles and distribution - Junqi Li; Yulong Ma; Yanli Li; Cuiping Jia; Ying Xiong; Bo Zhang; Stuart Harrad; Ke Du (Environmental Pollution, 2026)

Corrigendum to “Concentrations of perfluoroalkyl substances in sediments and wastewater treatment plant-derived biosolids from Ireland” [Science of the Total Environment, 979 (2025), 179380] - Yulong Ma; Martin Sharkey; Ann Marie Coggins; Will Stubbings; Mark G. Healy; Stuart Harrad (Science of The Total Environment, 2026)

Elucidating the role of microplastics as reservoirs of brominated flame retardants in river sediment - Jingxi Jin; Shijie Wang; Yulong Ma; Simeon Onoja; William A. Stubbings; Mohamed Abou-Elwafa Abdallah; Stuart Harrad (Journal of Hazardous Materials, 2026)

Microplastics in commercial food products from the United Kingdom market: Implications for human exposure - Muneera Al-Mansoori; Stuart Harrad; Mohamed Abou-Elwafa Abdallah (Environmental Research, 2026)

PBDE concentrations in wastes from construction and demolition, soft furnishings, and end-of-life vehicles in Brazil - Hansel David Burgos Melo; Juliana de Souza-Araujo; Rafael Cardoso; Daniele Frascareli; Erik Sartori Jeunon Gontijo; Sandro Donnini Mancini; Stuart Harrad; André Henrique Rosa (Environmental Research, 2025)

Organic ultraviolet filters in Irish sediments and biosolids - Martin Sharkey; Yulong Ma; Liu Yang; Stuart Harrad; Mark G. Healy; William A. Stubbings; Ann Marie Coggins (Science of The Total Environment, 2025)

Synthetic microplastics in hot and cold beverages from the UK market: Comprehensive assessment of human exposure via total beverage intake - Muneera Al-Mansoori; Stuart Harrad; Mohamed Abou-Elwafa Abdallah (Science of The Total Environment, 2025)

Pyrethroids in sediments and wastewater treatment plant-derived biosolids from Ireland - Shijie Wang; Martin Sharkey; Jingxi Jin; William Stubbings; Habib Bagheri; Mark G. Healy; Marie Coggins; Mohamed Abou-Elwafa Abdallah; Stuart Harrad (Science of The Total Environment, 2025)

Investigating the desorption of polybrominated diphenyl ethers from polyethylene microplastics to sediment - Jingxi Jin; Shijie Wang; Simeon Onoja; Yulong Ma; William A. Stubbings; Mohamed Abou-Elwafa Abdallah; Stuart Harrad (Science of The Total Environment, 2025)

Concentrations of perfluoroalkyl substances in sediments and wastewater treatment plant-derived biosolids from Ireland - Yulong Ma; Martin Sharkey; Ann Marie Coggins; Will Stubbings; Mark G. Healy; Stuart Harrad (Science of The Total Environment, 2025)

Antibiotics residues in inland and transitional sediments - Martin Sharkey; William A. Stubbings; Stuart Harrad; Mark G. Healy; Shijie Wang; Jingxi Jin; Ann Marie Coggins (Chemosphere, 2024)

Comprehensive characterization of European house dust contaminants: Concentrations and profiles, geographical variability, and implications for chemical regulation and health risk - Peter Haglund; Nikiforos A. Alygizakis; Adrian Covaci; Lisa Melymuk; Pernilla Bohlin Nizzetto; Pawel Rostkowski; Alexandre Albinet; Sylvana Alirai; Dagny Aurich; Stefan Bieber; Ana Ballesteros-Gómez; Amanda A. Brennan; et al. (Science of The Total Environment, 2024)

Legacy and emerging flame retardants in sediments and wastewater treatment plant-derived biosolids - Martin Sharkey; Shijie Wang; Stuart Harrad; William A. Stubbings; Mark G. Healy; Jingxi Jin; Ann Marie Coggins (Science of The Total Environment, 2024)

Microplastics in indoor air from Birmingham, UK: Implications for inhalation exposure - Hassan Khalid Ageel; Stuart Harrad; Mohamed Abou-Elwafa Abdallah (Environmental Pollution, 2024)

Organophosphate triesters and their diester degradation products in the atmosphere–A critical review - Shijie Wang; Jingxi Jin; Yulong Ma; William A. Stubbings; Muideen Remilekun Gbadamosi; Mohamed Abou-Elwafa Abdallah; Stuart Harrad (Environmental Pollution, 2024)

Interspecies comparison of metabolism of two novel prototype PFAS - Viktória Licul-Kucera; Oddný Ragnarsdóttir; Tobias Frömel; Annemarie P. van Wezel; Thomas P. Knepper; Stuart Harrad; Mohamed Abou-Elwafa Abdallah (Chemosphere, 2024)

The European Regulatory Strategy for flame retardants – The right direction but still a risk of getting lost - Jacob de Boer; Stuart Harrad; Martin Sharkey (Chemosphere, 2024)

Concentrations and legislative aspects of PBDEs in plastic of waste electrical and electronic equipment in Brazil - Hansel David Burgos Melo; Juliana de Souza-Araujo; Laura Geraldine Benavides Garzón; João Carlos Macedo; Rafael Cardoso; Sandro Donnini Mancini; Stuart Harrad; André Henrique Rosa (Science of The Total Environment, 2024)

Neural network for evaluation of the impact of the UK COVID-19 national lockdown on atmospheric concentrations of PAHs and PBDEs - André Henrique Rosa; William A. Stubbings; Olumide Emmanuel Akinrinade; Erik Sartori Jeunon Gontijo; Stuart Harrad (Environmental Pollution, 2024)

Dermal bioaccessibility of perfluoroalkyl substances from household dust; influence of topically applied cosmetics - Oddný Ragnarsdóttir; Mohamed Abou-Elwafa Abdallah; Stuart Harrad (Environmental Research, 2023)

Occurrence, source apportionment, and ecological risk assessment of organophosphate esters in surface sediment from the Ogun and Osun Rivers, Southwest Nigeria - Muideen Remilekun Gbadamosi; Adeyemi Lawrence Ogunneye; David Olaoluwa Jegede; Mohamed Abou-Elwafa Abdallah; Stuart Harrad (Environmental Science and Pollution Research, 2023)
Organophosphate esters (OPEs) are synthetic chemicals widely used as e.g., flame retardants and plasticisers in various consumer products. Due to the toxicity of OPEs in aquatic ecosystems, exposure of fauna and flora to these compounds is of potential concern. In this study, the concentrations, profiles, sources, and ecological risk of eight OPEs were investigated in the sediments from the two major rivers in southwest Nigeria. Concentrations of ∑OPEs in surface sediments were in the range 13.1 – 2110 ng/g dry weight (dw) (median: 378 ng/g dw) in the Ogun River and 24.7—589 ng/g dw (median: 174 ng/g dw) in the Osun River. These concentrations are broadly within the range of those reported in surface sediment in previous studies conducted in other locations around the world. Tris (2-butoxyethyl) phosphate (TBOEP) was the dominant OPE in the sediment samples with a median concentration of 337 and 126 ng/g dw for the Ogun and Osun Rivers respectively, while tri-n-butyl phosphate (TnBP) was not detected in any sample. Excluding TBOEP, the chlorinated organophosphate esters: tris(2-chloroethyl) phosphate (TCEP), tris(2-chloro-propyl) phosphate (TCIPP), and tris(1,3-dichloro-2-propyl) phosphate (TDCIPP) were the dominant OPEs in the Osun River, while the aryl-OPEs: triphenyl phosphate (TPHP), 2-ethylhexyl diphenyl phosphate (EHDPP), and tri- m -tolyl phosphate (TMTP) were dominant in the Ogun River. Under a median exposure scenario, moderate ecological risk was predicted from exposure to TCIPP in the Osun River. In contrast, under a high exposure scenario, concentrations of TDCIPP (risk quotient, RQ = 5.33—5.37) constituted a high ecological risk in both rivers, with moderate risks observed for TBOEP (RQ = 0.022—0.18) and TCIPP (RQ = 0.097 – 0.16). Therefore, the risk to aquatic organisms from concomitant exposure to mixtures of OPEs in freshwater ecosystems requires further investigation. Graphical Abstract

Are UK E-waste recycling facilities a source of environmental contamination and occupational exposure to brominated flame retardants? - Yulong Ma; Ester Konecna; Reginald Cline-Cole; Stuart Harrad; Mohamed Abou-Elwafa Abdallah (Science of The Total Environment, 2023)

Occurrence and dietary exposure to organophosphorus esters in foodstuffs of Nigerian origin - Muideen Remilekun Gbadamosi; Kehinde Hakeem Moberuagba; Mohamed Abou-Elwafa Abdallah; Stuart Harrad (Food Control, 2023)

Temporal trends in concentrations of brominated flame retardants in UK foodstuffs suggest active impacts of global phase-out of PBDEs and HBCDD - Yulong Ma; William A. Stubbings; Mohamed Abou-Elwafa Abdallah; Reginald Cline-Cole; Stuart Harrad (Science of The Total Environment, 2023)

Chlorinated organophosphate esters in Irish waste foams and fabrics: Concentrations, preliminary assessment of temporal trends and evaluation of the impact of a concentration limit value - Stuart Harrad; Martin Sharkey; William A. Stubbings; Misbah Alghamdi; Harald Berresheim; Marie Coggins; André Henrique Rosa; Daniel Drage (Science of The Total Environment, 2023)

Elevated concentrations of halogenated flame retardants in waste childcare articles from Ireland - Stuart Harrad; Daniel Drage; Martin Sharkey; Will Stubbings; Misbah Alghamdi; Harald Berresheim; Marie Coggins; André Henrique Rosa (Environmental Pollution, 2023)

Palaeotoxicity: reconstructing the risk of multiple sedimentary pollutants to freshwater organisms - Neil L. Rose; Simon D. Turner; Handong Yang; Congqiao Yang; Charlotte Hall; Stuart Harrad (Environmental Geochemistry and Health, 2018)

UK dietary exposure to PCDD/Fs, PCBs, PBDD/Fs, PBBs and PBDEs: comparison of results from 24-h duplicate diets and total diet studies - Lindsay Bramwell; David Mortimer; Martin Rose; Alwyn Fernandes; Stuart Harrad; Tanja Pless-Mulloli (Food Additives & Contaminants: Part A, 2017)

An introduction to environmental chemistry, 2 nd edition by Julian E. Andrews, Peter Brimblecombe, Tim D. Jickells, Peter S. Liss and Brian J. Reid, Blackwell Publishing, Oxford, 2004. 320 pages, ISBN 0632059052 (paperback) - Stuart Harrad (International Journal of Climatology, 2005)

Bioaccumulation Factors (BAFs) and Biota to Sediment Accumulation Factors (BSAFs) for PCBs in pike and eels - Stuart J. Harrad; David J. T. Smith (Environmental Science and Pollution Research, 1997)

The relative contribution of individual polychlorinated biphenyls (PCBs), polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzo-p-furans (PCDFs) to toxic equivalent values derived for bulked human adipose tissue samples from Wales, United Kingdom - Raquel Duarte-Davidson; Stuart J. Harrad; Susan Allen; Andrew S. Sewart; Kevin C. Jones (Archives of Environmental Contamination and Toxicology, 1993)